Cardioprotective role of salvia rosmarinus (rosemary) leaves against oxidative stress and in balancing lipid profile in mice. - Ghayas, Hina; Sohail, Sumera; Iqbal Khan, Nazish; Yasmeen, Ghazala; Naz, Lubna; Shamim, Mufzala (International Journal of Endorsing Health Science Research, 2021)
Background: Developing countries encounter a change in lifestyle, which establish novel risk factors for cardiovascular disease, leading to an explosion in cardiovascular disease risk all through the developing nations. Dietary therapies and physical activity are the first lines of treatment in hyperlipidemia, and several dietary components with such effects have been identified. This study is intended to assess the potential of Salvia Rosmarinus (SR) leaves powder consumption on diet-induced hyperlipidemia. The main objective of this study is to show that plant products could be equivalent to the available medicines. Methodology: In this experimental study, 4 to 5 weeks old mice were used with an average weight of 200 gm. Baseline values of all parameters were observed & animals were administered an atherogenic diet for two weeks. 0.11 gm/day rosemary leaves powder was fed by these hypercholesterolemic rats for another two weeks. At the end of the experimental duration, blood samples were collected and evaluated for alterations in plasma lipid profile, glucose, liver enzymes and kidney biomarkers. Results: According to the research results, oral supplementation of 0.11 gm/day rosemary effectively reduced dietary hyperlipidemia in experimental mice. Significant (p<0.05) reduction in body weights, total plasma cholesterol (TC), glucose, alkaline phosphate (ALP) and urea levels were analysed, and a non-significant decrease in triglyceride (TG), low-density lipoprotein (LDL), uric acid and creatinine was observed. Conclusion: It is concluded that Rosemary can be utilized beneficially for primary prevention trials of cardiovascular disease, but of course, further investigations are required to find out an effective dose of rosemary.